Flavored Cigars Appeal to Younger, Female, and Racial/Ethnic Minority College Students. Issue 3 (11th February 2017) - Hinds, Josephine T; Li, Xiaoyin; Loukas, Alexandra; Pasch, Keryn E; Perry, Cheryl L
Abstract: Introduction: This study examined the association of sociodemographic characteristics, tobacco and substance use behaviors, and reasons to use cigars in young adults' flavored and non-flavored cigar use. Methods: Participants were 523, 18- to 29- year-old young adult college students (60.4% male; 40.9% non-Hispanic white) who reported current (past 30-day) cigar use. Results: Almost 75% of the sample regularly chose flavored cigar products. Multilevel logistic regression analyses indicated that younger, female, and racial/ethnic minority cigar users had significantly greater odds of using flavored cigars than their counterparts. Current marijuana smokers, ever-blunt smokers, and students who reported using cigars because they were affordable and/or available in flavors they liked had a greater odds of flavored cigar use compared to their counterparts. Moreover, among dual users of cigars and cigarettes, those who cited using cigars because they were cheaper than cigarettes and because cigars felt like smoking regular cigarettes had greater odds of using flavored cigars compared to their peers. Number of days cigars were smoked and current use of other tobacco products were not associated with flavored cigar use. Conclusions: Appealing attributes of flavored cigars have the potential to contribute to the tobacco use and subsequent nicotine addiction of younger, female, and racial/ethnic minority young adults. The wide variety of cigar flavors, their attractive price, and similarity to cigarette smoking underscore the need for additional research that links these unique traits to sustained tobacco use, and underscore the need for regulation of flavored products. Implications: This study extends the current literature by finding that younger, female, and racial/ethnic minorities have greater odds of flavored cigar use than their peers. Flavored cigars have characteristics that appeal to members of these populations, which can contribute to their long-term use and potential for addiction.